The Influence of Professional Judgment and Whistleblowers on Fraud Prevention (A Study of BPKP Auditors in North Sumatra Province - Aris Setiono; M. Irsan Nasution; Renny Maisyarah (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of professional judgment and whistleblowers on fraud prevention among auditors at the Financial and Development Supervisory Agency (BPKP) of North Sumatra Province. Fraud in the public sector remains a serious problem, impacting low accountability and public trust, making the role of government internal auditors highly strategic. Professional judgment reflects the auditor's ability to use knowledge, experience, and professional judgment in the audit process, while whistleblowers serve as a reporting mechanism that supports early fraud detection and prevention. This study employed a quantitative approach with a survey method, where primary data were collected through questionnaires distributed to 60 BPKP auditors in North Sumatra Province. The data analysis technique used was Structural Equation Modeling–Partial Least Square (SEM-PLS). The results showed that professional judgment had a positive and significant effect on fraud prevention. Furthermore, whistleblowers were also shown to have a positive and significant effect on fraud prevention. These findings indicate that improving the quality of auditors' professional judgment and strengthening the whistleblower system and culture can increase the effectiveness of fraud prevention in government. This study is expected to provide theoretical contributions to the development of public sector auditing literature and practical implications for BPKP in formulating policies to improve audit quality and control fraud